Hippocrates On Ancient Medicine : Translated with Introduction and Commentary. - Schiefsky, Mark J. (Studies in ancient medicine, 2006)
This volume presents an up-to-date Greek text of the Hippocratic treatise On Ancient Medicine along with a new English translation, a detailed commentary focusing on questions of medical and scientific method, and an introduction that places the work in its intellectual context.